2015
DOI: 10.1177/0022034515572021
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Medication-related Osteonecrosis of the Jaw

Abstract: Medication-related osteonecrosis of the jaw (MRONJ), although initially believed to be exclusively associated with bisphosphonates, has been implicated in recent reports with additional drugs, especially the bone antiresorptive denosumab. The pathophysiology has not been fully elucidated, and no causal association between bone antiresorptive regimens and MRONJ has yet been established. However, reduced bone turnover and infection, an almost universal finding, are thought to be central to the pathogenesis of MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 50 publications
1
86
0
14
Order By: Relevance
“…Alternatively, the presence of osteonecrosis in the maxilla and mandible could be because of a unique response of the jaws versus other bones to the harmful inflammatory environment. Such a heightened sensitivity could explain the near exclusive presentation of ONJ in the jaws compared with the remaining skeleton …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the presence of osteonecrosis in the maxilla and mandible could be because of a unique response of the jaws versus other bones to the harmful inflammatory environment. Such a heightened sensitivity could explain the near exclusive presentation of ONJ in the jaws compared with the remaining skeleton …”
Section: Discussionmentioning
confidence: 99%
“…1. 25 MRONJ is more prevalent and severe in patients with comorbidities such as cancer or immunosuppression, and clinical suppuration and oral trauma have been shown to be independent risk factors for disease onset. 26 MRONJ is also known to be associated with bacterial biofilms, making treatment more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the presence of Actinomyces colonies in biopsy material from patients with MRONJ, suggesting that these bacteria contribute to MRONJ-associated infections (2,45,46). Members of the Actinomyces genus are filamentous, gram-positive and anaerobic bacteria that typically colonize the mouth, colon and vagina.…”
Section: Discussionmentioning
confidence: 99%